School Heads’ Supervision Practices and Teachers’ Instructional Performance: Basis for a Proposed Mentoring Program - Desiree Mislang-Sison; Armando Junio (ASEAN Multidisciplinary Research Journal, 2019)
This study aimed to determine the relationship between school heads’ supervision practices and teachers’ instructional performance as basis for a proposed mentoring program.The findings of the study reveal that most of the teachers are 25 to 40 years old which has the most number of frequency and most are aged above 40 years.. In terms of sex, female teachers and school heads are more dominant than males .When it comes to civil status, most of the teachers and school heads are married. In terms of educational attainment,most of the teachers earned their units in Master’s Degree while most of the school heads PhD/EdD holder. School heads and teachers are serving the public for less than 10 years and 10 to 30 years. In terms of specialization, most of the teachers are English majors while school heads are Mathematics majors. In terms of position, most of the principal are Principal I and teachers are Teacher III. Both teachers and school heads are members of professional organization ,do not have any other designations, attended series of seminars and with plus factors.The level of teachers’ instructional performance along content knowledge and pedagogy, learning environment and diversity of learners, curriculum and planning and assessement and reporting is Very Satisfactory.On the other hand, the level of school heads’ supervision practices along instructional supervision, learning environment, human resource management and development and parents’ involvement and community partnership and school leadership management and operations is outstanding. Supervision practices of school heads varies when they are grouped as to position, seminars attended and plus factor while nstructional performance of teachers varies when they are grouped according to educational attainment, length of service and position.Moreover, instructional supervision established a positive correlation with content knowledge and pedagogy while learning environment, school leadership and management operations established a positive correlation with learning environment, diversity of learners and curriculum and planning.